Importance of Pollinators in Fruit Production: A Review - Singh, Amardeep; Adhikary, Trina (International Journal of Economic Plants, 2021)
Pollinators play a pivotal role in the pollination of a variety of crop species. Pollination, especially by insects, is a critical component of ecosystem functioning and thus constitutes a globally important ecosystem service. Not only plant sexual reproduction is assured, but yields are also stabilized and seed genetic diversity is preserved, preventing inbreeding depression and enhancing system resilience. More than 1300 plant species are thought to be grown for fruit, drinks, medicines, condiments, spices, and even cloth around the world. Animals pollinate about 75% of these species. In reality, pollinators such as bees, birds, and bats affect 35% of global crop production, resulting in increased yields of 87 of the world’s most important food crops. Honey bees are the prime pollinators of the world’s angiosperms, pollinating about 66% of the 1500 crop species and contributing 15–30% of global food supply. For the pollinators who visit them, the form of flower, shape, colour, odour, nectar, and composition are all critical. To ensure pollination, many fruit crops need an insect pollinator. Pollinators boost the quantitative and qualitative characteristics of a wide variety of fruit crops. It is critical to comprehend the significance of pollinator species diversity in their natural environment.